Professional Use and Teaching of UML: Perceptions of Brasília-DF Region Software Practitioners and Higher Education Instructors - Canedo, Edna Dias; OliveiraJr, Edson; Tives, Heloise Acco (Anais do Workshop sobre Educação em Computação (WEI); 2025: Anais do XXXIII Workshop sobre Educação em Computação, 2025)
Context: UML remains a widely recognized modeling language in software engineering education and industry. However, its adoption and teaching effectiveness face challenges related to complexity, time constraints, and alignment with industry practices. Understanding how UML is currently taught and used in professional settings is important for improving its role in software development. Goal: This study investigates how UML is taught in higher education and used in industry in Brasília-DF, identifying the most emphasized diagrams, key motivations for its adoption, and the challenges faced by educators and practitioners. Methods: We conducted a survey with 21 instructors and 51 software practitioners to analyze which UML diagrams are most frequently taught and used, how UML is applied in software projects, and what factors influence its adoption or rejection. The study combined quantitative analysis of closed-ended questions and qualitative coding of open-ended responses to provide a comprehensive perspective. Results: The findings indicate that class, use case, and sequence diagrams are the most commonly taught and emphasized in academia. Instructors value UML for its role as a communication standard and learning tool, but complexity, lack of time, and tool availability are major barriers to effective teaching. In industry, UML is primarily used for problem modeling and system flow representation, but semantic complexity, difficulty in maintaining updated documentation, and lack of training limit its widespread adoption. Many companies prefer simpler alternatives, such as flowcharts and data flow diagrams.